Road to Emancipated Curriculum: The Transformation of Teacher Mindset Regarding the Preparation of Teaching Module - Muhammad Sandy Al Fath; Putri, Nikmah Sistia Eka; Setiani, Fatimah (Amala Jurnal Pengabdian Kepada Masyarakat, 2024)
Education transformation requires teachers to make changes on all fronts. Not The exception to the mindset in the concept of an independent curriculum is one of the real forms that requires teachers to face existing changes. This community service activitywas carried out at MTsN 1 Kotawaringin Barat where a vital problem was found with the lack of information about the concept of this independent curriculum, aiming to provide understanding and preparation to teachers in implementing the independent curriculum through counseling and mentoring methods by delivering theories about curriculum concepts and appropriate student assessment. This activity was attended by 40 teachers of MTsN 1 Kotawaringin Barat. The results of the implementation of this service activity are 1) Providing material on teaching concepts in the independent curriculum, especially project-based differentiated teaching 2) Providing material about the type of assessment used. The target and output of this activity is the formation of a new mindset that can help teachers in carrying out their duties later. Based on the results of evaluating the implementation of activities to determine the effectiveness of delivery, it can be concluded that this service activity shows a significant increase in knowledge after providing counseling material as indicated by an increase in the average post-test score.